Chondromyxoid fibroma of the iliac bone: a brief radiological review. Issue 11 (29th November 2022) - Alsford, Samuel; Low, Samantha; Mistry, Alpesh
Abstract : Chondromyxoid fibroma (CMF) is a rare, benign bone tumour most commonly located within the metaphyseal region of the long bones surrounding the knee joint. Here, we present an interesting case of a young woman in her early 20s with CMF of the left iliac bone and include a literature review of comparable studies with an emphasis on radiological findings and important differential diagnoses to be aware of in this atypical location.